2018
DOI: 10.1007/s10877-018-0187-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a mobile app for reducing errors of administration of medications in an emergency

Abstract: Medication errors occur frequently and are a risk to patient safety. To reduce mistakes in the medication process in emergencies, a mobile app has been developed supporting the calculation of doses and administration of drugs. A simulation study was performed to validate the app as a tool to reduce medication errors. This was a randomised crossover study conducted in the Academic Hospital. The participants included were residents and attendings in anaesthesiology. 74 Participants performed four simulation scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 23 publications
0
27
0
6
Order By: Relevance
“…Various studies [12][13][14][15][16] have shown that information and communication technology, particularly mobile devices, is used in all areas of health care, including drug dosage calculations. Currently, many people of different medical professions are using different mobile health applications and these have a positive effect on their activities and performance [15,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies [12][13][14][15][16] have shown that information and communication technology, particularly mobile devices, is used in all areas of health care, including drug dosage calculations. Currently, many people of different medical professions are using different mobile health applications and these have a positive effect on their activities and performance [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…As ICU nurses are on the shift when administrating medication to the patient, they need a tool that can provide information quickly and easily. Studies which have used information and communication technology for drug dosage calculations involve anesthesiologists using mobile health applications [13], mobile health application for calculating drugs in pediatric cardiovascular resuscitation [25], and CPOE implementation [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile apps or other mHealth solutions are being developed for many different interventions in healthcare. There has been a recent and significant increase in the development of solutions aiming to reduce errors surrounding prescription and drug administration [ 7 , 8 ]. This kind of technological intervention is easy to target, rather fast to develop and can lead to significant improvements in clinical practice and patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them suggest doses that might exceed the maximum safe dose and give only general advice as to the caution with which their propositions should be used. The successful use of specific mobile health (mHealth) point of care decision-support tools focusing on drug administration has been described in other contexts, such as emergency settings [ 7 ], simulated pediatric cardiopulmonary resuscitation [ 8 ], as well as for the prescription of antibiotics [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, anesthesiologists have historically used smartphones to calculate drug dosages. Baumann et al compared the probability of administering accurate medication dosages in emergency simulations with a dosage calculator app versus without it [ 21 ]. The probability of an accurate dose administration was higher in the app group compared to the control group (94%, SD 90-97.8 vs 77.7%, SD 70.9-84.5) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%